Perceptions of educational interpreting at SU: Towards a more informed and supportive interpreting service - Brewis, Carmen; Lotter, Risha; De Kock, Eduard; De Jager, Sanet; Botha, Tania; Wheeler, Rene; Van den Berg, Nanette (Stellenbosch Papers in Linguistics Plus, 2023)
This article reports on a study conducted in October 2019 by the interpreters in the research portfolio of Stellenbosch University’s interpreting service. The study tested student perceptions of interpreting in authentic interpreted lectures amongst two subsets of users: those listening to interpreting in English, mostly out of necessity, and those who listen to interpreted lectures in Afrikaans, largely by choice.[1] The research project was undertaken to gain a better understanding of the value that student users take from the service, and how it helps or hinders their learning. Interpreters wanted to gain insight into their users’ evolving needs and into the role that they themselves can play in addressing these. The article concludes by recommending practical measures to support students who feel lost and helpless due to a language deficit in the language of instruction. The outcome of the investigation shows the value of interpreting for some, but also the complications and frustration experienced by users in interpreted lectures. It highlights the necessity of thinking differently about our practices and about how these may be adapted in order to meet our users’ needs. Significantly, the results suggest the need for an expanded and more active role for interpreters in and outside the classroom. It also calls for closer collaboration between interpreters, their users and lecturers, which is necessary to negotiate and formalise the terms of a shared learning space. If interpreters are to facilitate meaning-making and understanding for their users in an increasingly remote online application, then innovative measures and in-depth planning will be needed to determine how to achieve this. Through these measures, what is currently a mainly theoretical objective can be converted into the reality of multilingual teaching and learning practices at South African universities. [1] This phenomenon is supported by the data and is discussed in par. 4.1.